Investigating Malaysian teachers' technology acceptance towards integrating e-learning into English teaching - Ke Hu; Asmaa AlSaqqaf (Journal of English Language Teaching Innovations and Materials (Jeltim), 2021)
The presence of e-learning is prevalent in the teaching and learning process over the world. It has been proven to have a significant impact on the teaching of English subject. Therefore, this paper aims at investigating the level of ESL teachers’ technology acceptance towards integrating e-learning into English teaching at secondary schools in Sabah, Malaysia, by examining the constructs of Perceived Usefulness (PE), Perceived Ease of Use (PEOU), Attitude towards Usage (ATU), and Behavioral Intention (BI), which were extracted from the Technology Acceptance Model (TAM) proposed by Davis. A number of 144 English language teachers from 18 secondary schools in Kota Kinabalu responded to an online cross-sectional survey based on a simple random sampling, whereas the collected data were analyzed quantitatively and statistically. Overall, the results indicated that ESL teachers had a high level of technology acceptance (mean=3.921) to use e-learning in teaching English in terms of their PU (mean=3.925), PEOU (mean=3.797), ATU (mean=4.007), and BI (mean=3.995) in particular. Moreover, the discussions, recommendations, and implications have also been given in response to the issues addressed in the study.